Expression of Hyaluronan Synthase 1 and Distribution of Hyaluronan During Follicular Atresia in Pig Ovaries1 - Miyake, Yuko (Society for the Study of Reproduction, 2009)
CD44 on macrophages is recognized as a phagocytic receptor involved in the phagocytosis of apoptotic cells. Recently, we detected CD44 on macrophages in atretic follicles during atresia. In this study, we evaluated the distribution of the principal CD44 ligand hyaluronan (HA) and the expressions of HA synthases (HAS: HAS1, HAS2, and HAS3) during atresia in pig ovaries. We determined the 2139-bp sequence of Sus scrofa HAS1 and raised an anti-HAS1 polyclonal antibody. The S. scrofa HAS1 sequence contained six putative HA-binding motifs and conserved amino acid residues crucial for GlcNac transferase activity. HAS1 mRNA expression was upregulated during atresia; however, HAS2 and HAS3 mRNA expression levels were low and very low to undetectable, respectively. Western blotting showed that HAS1 was markedly upregulated during atresia. Immunohistochemical analyses revealed HAS1 distribution in theca cells of healthy and early atretic (stages I and II) follicles and in progressing atretic (stage III) follicles. Hyaluronan was visualized with the HA-binding protein; it accumulated in the theca layer during all stages and in stage III follicles. Hyaluronan assay showed a significantly increased HA concentration in follicular fluid at stage III. Flow cytometry showed HAS1 expression in 55.7% of SIRPA-positive macrophages in stage III follicles. Our results suggest that the HA concentration in follicular fluids increased during atresia and that HAS1 may be the dominant HAS protein in theca cells to produce HA in pig ovaries.